2002
DOI: 10.1046/j.1365-2141.2002.03843.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and nature of CD20‐negative relapses following rituximab therapy in aggressive B‐cell non‐Hodgkin's lymphoma: a retrospective review

Abstract: Summary. Re-treatment with rituximab for B-cell nonHodgkin's lymphoma (NHL) relapsing after previous rituximab therapy has recently been shown to be clinically efficacious. Although the mechanism of resistance to rituximab re-treatment in non-responding patients is unknown, it is possible that loss of CD20 expression in the relapsed NHL could be important in some patients. We examined the incidence and nature of CD20 negative relapses following rituximab therapy in aggressive B-cell NHL treated at our institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 11 publications
3
86
0
3
Order By: Relevance
“…3,4 There are two emerging issues to be resolved for better usage of this drug: weak effects on some tumors [6][7][8] and drug resistance. 5,[9][10][11] In this study, we clearly demonstrated that HDAC inhibitors, VPA and romidepsin, potentiated the cytotoxic effect of rituximab against Burkitt lymphoma, which has innate resistance to rituximab, 7 by enhancing the expression of surface CD20 antigen both in vitro and in vivo. We also analyzed the mechanisms of CD20 upregulation and found that HDAC inhibitors acetylated core histones of CD20 promoter to enhance the binding of Sp1, leading to transactivation of the CD20 gene in BJA-B and Namalwa cells.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…3,4 There are two emerging issues to be resolved for better usage of this drug: weak effects on some tumors [6][7][8] and drug resistance. 5,[9][10][11] In this study, we clearly demonstrated that HDAC inhibitors, VPA and romidepsin, potentiated the cytotoxic effect of rituximab against Burkitt lymphoma, which has innate resistance to rituximab, 7 by enhancing the expression of surface CD20 antigen both in vitro and in vivo. We also analyzed the mechanisms of CD20 upregulation and found that HDAC inhibitors acetylated core histones of CD20 promoter to enhance the binding of Sp1, leading to transactivation of the CD20 gene in BJA-B and Namalwa cells.…”
Section: Discussionmentioning
confidence: 56%
“…8 Furthermore, several cases of CD20-negative relapse were identified after treatment with rituximab-based regimens in diffuse large B-cell lymphoma. 9,10 Recently, Hiraga et al 11 reported that relapse or disease progression was observed in B30% of patients with B-cell lymphomas treated with rituximab-containing chemotherapies, and CD20 expression was lost in 5 of 19 relapsed patients who underwent repeated biopsy. It is of note that DNAdemethylating agents restored CD20 expression in lymphoma cells isolated from these patients, suggesting that epigenetic mechanisms underlie the downregulation of CD20 after rituximab treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Because scFvRit:sFasL directly induces apoptosis, which solely requires the cross-linking of CD20 and Fas, scFvRit:sFasL may be particularly relevant for patients with poor or absent complementdependent cytotoxicity. In addition, treatment with rituximab has been proposed to lead to the development of CD20-negative relapses in some patients, possibly due to tumor cell heterogeneity (25,26). For scFvRit:sFasL, the reciprocal activation of Fas by CD20-immobilized scFvRit:sFasL opens up the possibility to induce apoptosis in neighboring FasL-sensitive leukemic cells that have lost CD20 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if CD20 expression alone determined rituximab responsiveness, then one would expect development of CD20-negative relapses after rituximab treatment, and this circumstance has rarely been reported, at least for indolent lymphoma (Davis et al, 2000). Recent reports are perhaps suggestive that CD20-negative relapses may develop in aggressive lymphomas (Davis et al, 1999;Foran et al, 2001;Kennedy et al, 2002), but care must be taken to differentiate true CD20 negativity from false-negative results attributable to blocking of labeled CD20 antibody by bound rituximab. There have been attempts to upregulate CD20 to try to enhance rituximab efficacy, such as with G-or GM-CSF, but mechanisms other than CD20 upregulation may account for any enhanced effect (Ravetch and Lanier, 2000;van der Kolk et al, 2002).…”
Section: Rituximab Distributionmentioning
confidence: 99%